Farmers' knowledge of the cultivation, economic and nutritional value of radish crop in Iseyin local government area of Oyo State (2019)
Fruits and vegetables are important as essential building blocks of any diet. They are loaded with vitamins and minerals. Although, many fruits and vegetables are cultivated, there are yet several others (exotic) with nutritional and economic potentials which farmers' attention has not been drawn to. Meanwhile, farmers in Iseyin Local Government Area (LGA) of Oyo state have commenced cultivation of radish crop. Therefore, the study assessed rural farmers' knowledge on the nutritional and economic value of radish (Raphanus sativus L. Family: Brassicaceae) crop in Iseyin LGA of Oyo state in order to boost production and consumption of this vegetable among Nigerians for healthy living. A total of 105 respondents were sampled through the Snowball Technique. Data collected through interview schedule were analyzed using both descriptive (frequencies, percentages) and inferential statistics (Chi-square and PPMC). Findings revealed that the average age of respondents was 47 years, 76.2% were male, 98.1% were married and 94.3% had at least one level of formal education. Household size of the majority (81.0%) and farming experience (92.4%) ranged between 6-8 persons and 20-25 years, respectively. Of all the sampled respondents, 87.6% cultivated Daikon or Japanese radish. Most respondents' source of information was mainly through friends (96.2%). Result further showed that 66.7% and 85.7% of the respondents had favourable perception and average knowledge on radish crop, respectively. 2 Respondents' level of education (χ = 89.638, p ≤0.05), sources of information (r = 0.658, p≤0.05), perception (r = 0.645, p ≤0.05) were significantly related to knowledge on the nutritional and economic value of radish crop. Knowledge level on the nutritional and economic value of radish crop cultivation was average among 85.7% of the respondents. Thus, there is need for government, through her extension agency to provide more awareness on the nutritional and economic values of radish crop to cultivators and general public at large.